PSYCHOLOGYCAL WELL BEING DALAM Q.S. AT-TI>N - Fachiatuzahro (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2022)
This article aims to explore the theory of Psychological Well-Being contained in Surah At-Ti>n. The method used in this research is a qualitative method which is supported by library research. While the interpretation method used is the maudu'i interpretation method. The results of the study found that in Surah At-Ti>n there are three aspects related to the theory of Psychological Well-Being, namely self-acceptance, environmental mastery, and purpose in life.